Stability of versions of the Weyl-type theorems under tensor product - Prasad, T.; Rashid, M. H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the transformation versions of the Weyl-type theorems from operators T and S for their tensor product T S in the infinite-dimensional space setting.